“Is It Removed During Dialysis?”—Cognitive Dysfunction in Advanced Kidney Failure—A Review Article - Crowe, Kirsty; Quinn, Terence J.; Mark, Patrick B.; Findlay, Mark D. (Frontiers in Neurology, 2021)
Cognitive impairment is independently associated with kidney disease and increases in prevalence with declining kidney function. At the stage where kidney replacement therapy is required, with dialysis or transplantation, cognitive impairment is up to three times more common, and can present at a younger age. This is not a new phenomenon. The cognitive interactions of kidney disease are long recognized from historical accounts of uremic encephalopathy and so-called ‘dialysis dementia’ to the more recent recognition of cognitive impairment in those undergoing kidney replacement therapy (KRT). The understanding of cognitive impairment as an extra-renal complication of kidney failure and effect of its treatments is a rapidly developing area of renal medicine. Multiple proposed mechanisms contribute to this burden. Advanced vascular aging, significant multi-morbidity, mood disorders and sleep dysregulation are common in addition to the disease-specific effects of uremic toxins, chronic inflammation and the effect of dialysis itself. The impact of cognitive impairment on people living with kidney disease is vast ranging from increased hospitalization and mortality to decreased quality of life and altered decision making. Assessment of cognition in patients attending for renal care could have benefits. However, in the context of a busy clinical service, a pragmatic approach to assessing cognitive function is necessary and requires consideration of the purpose of testing and resources available. Limited evidence exists to support treatments to mitigate the degree of cognitive impairment observed, but promising interventions include physical or cognitive exercise, alteration to the dialysis treatment and kidney transplantation. In this review we present the history of cognitive impairment in those with kidney failure, current understanding of the mechanisms, effects, and implications. We provide a practical approach to clinical assessment and discuss evidence-supported treatments and future directions in this ever-expanding area which is pivotal to our patients’ quality and quantity of life.